Isolation and complete genome characterization of novel reassortant orthoreovirus from common vole (Microtus arvalis) - Fehér, Enikő; Kemenesi, Gábor; Oldal, Miklós; Kurucz, Kornélia; Kugler, Renáta; Farkas, Szilvia L.; Marton, Szilvia; Horváth, Győző; Bányai, Krisztián; Jakab, Ferenc (Virus genes, 2017)
A novel mammalian orthoreovirus (MRV) strain was isolated from the lung tissue of a common vole ( Microtus arvalis ) with Tula hantavirus infection. Seven segments (L1–L3, M2–M3, S2, and S4) of the Hungarian MRV isolate MORV/47Ma/06 revealed a high similarity with an MRV strain detected in bank vole ( Myodes glareolus ) in Germany. The M1 and S3 segment of the Hungarian isolate showed the closest relationship with the sequence of a Slovenian human and a French murine isolate, respectively. The highest nucleotide and amino acid identity values were above 90 and 95% in all of the comparisons to the reference sequences in GenBank, except for the S1 with a maximum of 69.6% nucleotide and 75.4% amino acid identity. As wild rodents are among the main sources of zoonotic infections, the reservoir role of these animals and zoonotic potential of rodent origin MRVs need to be further investigated.